2019
DOI: 10.21608/mjcu.2019.76635
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bladder Neoplastic Masses Findings through Multidetector-Row CT Urography

Abstract: Background: Urinary bladder carcinoma is one of the most common tumors among the lower urinary tract, it is the seventh common malignancy and widely distributed in developed countries. Aim of Study: To elucidate the diagnostic potential and additive imaging data obtained with Multi-Detector Computed Tomography (MDCT) in early detection and characterization of urinary bladder neoplastic masses by comparing the result of the study with the conventional cystoscopy results. Patients and Methods: This prospective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In pre-contrast study, no cases were detected while in post-contrast study 4 cases (13.3%) were found to have pelvic or parailiac lymph node enlargement. As compared to the results of Ola et al, [1] . Regional lymph nodes were identified in post-contrast CT study in 6 out of 30 cases (20%).…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…In pre-contrast study, no cases were detected while in post-contrast study 4 cases (13.3%) were found to have pelvic or parailiac lymph node enlargement. As compared to the results of Ola et al, [1] . Regional lymph nodes were identified in post-contrast CT study in 6 out of 30 cases (20%).…”
Section: Discussionmentioning
confidence: 59%
“…In our study, the perivesical fat stranding was found in 8 cases (26.7%) in post-contrast study that was not properly identified in the pre-contrast study. In the study done by Ola et al, [1] , perivesical fat stranding was found in 11 cases (36.7%) that was also identified in only the post-contrast studies.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations